Pendidikan Kesehatan pada Ibu Hamil dan Nifas tentang Asi Ekslusif untuk Meningkatkan Cakupan Asi Ekslusif - Winda Nurmayani M; Syamdarniati Syamdarniati; Misroh Mulianingsih; Indah Wasliah; Sopian Halid (Poltekkes Kemenkes Surakarta, 2020)
Background: The Indonesian government has targeted exclusive breastfeeding 80%, but exclusive breastfeeding is not widely done, although the benefits of exclusive breastfeeding are very many, especially for babies and mothers, but in fact many mothers do not give exclusive breastfeeding to their babies, and in the field many mothers stop giving Breast milk in her baby before the age of 2 years. The process of early breastfeeding does not always run smoothly, sometimes mothers and babies experience various obstacles that hinder or complicate the process of breastfeeding, especially if this is the first experience for primigravida mothers who are still young and have a low level of knowledge about breastfeeding that hinders the practice of breastfeeding, and usually her child is not yet 2 years old ASI has been discontinued (Dewanetal., 2002; Yanikkeremetal., 2009). The purpose of this community service is to educate pregnant and post-partum mothers how to properly care for breast and breastfeeding techniques in an effort to increase exclusive breastfeeding coverage. Methods: This community service method is carried out by means of counseling in delivering material then followed by demonstrations and Q&A sessions. Results: The results of this dedication appear to be still many pregnant women and postpartum mothers who do not know the benefits of exclusive breastfeeding, how to care for the breast and how to breastfeed the right baby techniques, after health promotion and demonstration it appears that pregnant women and postpartum mothers are serious in understanding every step demonstrated. . Conclusion: Based on the results of the service, it is hoped that this activity can increase the coverage of breastfeeding mothers so that they can provide exclusive breastfeeding to their babies.